The historical and political significance of the reconstruction of the Cathedral of Christ the Saviour in Moscow - Préneuf, FM; Préneuf, FM (1997)
A cathedral appeared in the centre of Moscow almost overnight. Where did it come from? Today’s cathedral of Christ the Saviour is perceived as a chudo, a ‘miracle’, because it is the re-appearance of a building last seen in 1931. In the intervening years it was one of the "blank spots” in official Soviet history. The way silence was broken and information about the cathedral became widespread, is part of the case I wish to make, but, for the purpose of this introduction, a very brief summary of the cathedral’s biography is useful. Tsar Alexander I, in a Manifesto issued on 25 December 1812, vowed to found a cathedral named Christ the Saviour, to thank God for having saved Russia from ruin in the hands of Napoleon's numerous and fierce troops; the church was also meant to uphold eternally for future generations the memory of "the unprecedented zeal, loyalty and love towards Faith and Fatherland" displayed by the Russian people in the course of battle. The young artist Alexander Vitberg was the architect of a first project, a classical-looking church composed of three parts expressing the trinity of suffering, death, and eternal life. To accommodate its colossal size (matching Russia's grandeur), it was located on Vorob’evy Gory (Sparrow Hills), across the river from the Kremlin. But the project foundered amid financial scandals and allegations of technical incompetence. Continued in thesis ...